Femtosecond Excited State Studies of the Two-Center Three-Electron Bond Driven Twisted Internal Charge Transfer Dynamics in 1,8-Bis(dimethylamino)naphthalene - Balkowski, Grzegorz; Szemik-Hojniak, Anna; van Stokkum, Ivo H. M; Zhang, Hong; Buma, Wybren J (The journal of physical chemistry. A, Molecules, spectroscopy, kinetics, environment, & general theory, 2005)
Femtosecond fluorescence upconversion and transient absorption experiments have been performed to monitor the photoinduced electronic, geometry, and solvent relaxation dynamics of 1,8-bis(dimethylamino)naphthalene dissolved in methylcyclohexane or n-hexane, n-dodecane, dichloromethane, and acetonitrile. The data have been analyzed by using a sequential global analysis method that gives rise to species associated difference spectra. The spectral features in these spectra and their dynamic behavior enable us to associate them with specific processes occurring in the molecule. The experiments show that the internal charge-transfer lπ* state is populated after internal conversion from the 1La state. In the lπ* state the molecule is concluded to be subject to a large-amplitude motion, thereby confirming our previous predictions that internal charge transfer in this state is accompanied by the formation of a two-center three-electron bond between the two nitrogen atoms. Solvent relaxation and vibrational cooling in the lπ* state cannot be separated in polar solvents, but in apolar solvents a distinct vibrational cooling process in the lπ* state is discerned. The spectral and dynamic characteristics of the final species created in the experiments are shown to correspond well with what has been determined before for the relaxed emissive lπ* state.